A organização do processo legislativo na Assembléia Legislativa do Rio Grande do Norte - Oliveira, Domingos Sávio Silva de (2005)
This work evaluates the organization of the legislative activities and the decision-making process within the Legislative Assembly of RN, emphasizing the role of ruling institutions on the Legislative Power working, as well as the structure of its decisions. The organization and the production of the decision-making process inside the Legislative Assembly will be seen along with how institutional norms determine the nature of the legislative process and influence his legal production. The period under study extends from 1990/94 to 1994/97 legislatures. The work is divided in three parts. The first analyzes the legislative process, the role of legal production, the nature of the legislation produced during the time referred and the role of the decisory instances: the directive Table, the leaders collegiate and the permanent commissions; the second part will present the results of questionnaires made to the deputies about their perspective concerning the actual power structure, as well as a more desirable power distribution among different decisory instances in the Assembly. At last, part three will focus on the Executive power role exerted on the legislative process, analyzing how it makes use of his initiating and veto prerogatives, via the study of some laws sanctioned in 1990-1997